Low Cycle Response Analysis of Welded Aluminum Alloy Box Castellated Beam. Issue 2 (April 2021) - Li, Chenghua; Gao, Yalin; Yang, Kaiyuan; Wang, Xi
Abstract: Welding aluminum alloy 6061-t6 aluminum alloy material is more and more widely used in construction engineering due to its light weight and high strength characteristics. Welding aluminum alloy box Castellated beam has great application value due to its unique section characteristics, in order to obtain more low cycle response curve of welding aluminum alloy box Castellated beam. In this paper, the constitutive relationship of domestic 6061-T6 aluminum alloy was obtained by laboratory test, and the finite element results were verified by low-cycle cycle test and full-scale test. ANSYS software is used to simulate the mechanical response of four welded aluminum alloy box Castellated beams under low cyclic load. The numerical results show that the hysteretic curves of aluminum alloy specimens are full, the pinching phenomenon is not obvious, and the welded aluminum alloy box Castellated beam shows strong overall stability. The seismic performance of welded aluminum alloy box Castellated beam is mainly controlled by expansion ratio, web height to thickness ratio and flange width to thickness ratio.